The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1034/j.1600-0420.1998.760607.x
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green angiography in isolated primary retinal arterial macroaneurysms

Abstract: ABSTRACT.Purpose: The study was carried out to describe the indocyanine green angiographic findings in isolated primary retinal arterial macroaneurysms and their contribution to the diagnosis of this condition. Methods. Fluorescein and indocyanine green angiography examination techniques were used to study isolated primary retinal arterial macroaneurysms in 8 consecutive patients with retinal or preretinal haemorrhage over a period of 12 months. Results. The fluorescein angiography examination showed the macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In the cases where hemorrhage blocks visualization of RAM in fundus photograph and the diagnosis with FA image is also not conclusive, ICGA is especially beneficial in that it can pinpoint the exact location of the RAM in such cases. [ 5 38 39 40 41 42 43 44 45 ] In the present report, all cases were clearly and correctly diagnosed by using all those methods. We think that an organic combination of those methods can guaranty the diagnosis.…”
Section: Discussionsupporting
confidence: 64%
“…In the cases where hemorrhage blocks visualization of RAM in fundus photograph and the diagnosis with FA image is also not conclusive, ICGA is especially beneficial in that it can pinpoint the exact location of the RAM in such cases. [ 5 38 39 40 41 42 43 44 45 ] In the present report, all cases were clearly and correctly diagnosed by using all those methods. We think that an organic combination of those methods can guaranty the diagnosis.…”
Section: Discussionsupporting
confidence: 64%
“…Up to now, the most reliable and common methods for detection of RAMs have been ICG and fluorescein angiography (FA) [ 1 , 17 ]. However, we achieved noninvasive detection of RAMs without dye injection in all our cases by means of SSADA based OCT angiography.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of blood, hard exsudates and/or dye leakage may impair their visualization by fundus photography and/or fluorescein angiography (FA) [3]. It has previously been shown that indocyanine green angiography (ICGA) may be useful for the detection of microaneurysms [6] and of arterial MAs [7][8][9][10]. To our knowledge, there is no reported data on the prevalence of MAs during diabetic retinopathy (DR).…”
Section: Introductionmentioning
confidence: 98%